2023
DOI: 10.1111/jch.14621
|View full text |Cite
|
Sign up to set email alerts
|

Reductions in systolic blood pressure achieved by hypertensives with three isometric training sessions per week are maintained with a single session per week

Abstract: Isometric handgrip or (wall) squat exercise performed three times per week produces reductions in systolic blood pressure (SBP) in adults with hypertension. We aimed to compare these interventions and the potential to retain benefits with one exercise session per week. We compared blood pressure changes following handgrip and squat isometric training interventions with controls in a randomized controlled multicentre trial in 77 unmedicated hypertensive (SBP ≥ 130 mmHg) adults. Exercise sessions were performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 29 publications
0
1
0
Order By: Relevance
“…Vale ressaltar que os treinos de resistência isométrica (TRI) possuem grande impacto na redução da pressão arterial (PA), de tal forma que podem ser usados na associação terapêutica, mas o seu benefício pode variar de acordo com o exercício praticado. A preensão palmar isométrica e agachamento na parede são exercícios que foram capazes de reduzir de forma semelhante os níveis de pressão arterial, sendo ambos praticados três vezes na semana, mas quando se reduziu a frequência para apenas uma vez na semana, somente o agachamento na parede foi capaz de manter seus benefícios e até mesmo progredir na queda da PA (Cohen, et al, 2023).…”
Section: Resultsunclassified
“…Vale ressaltar que os treinos de resistência isométrica (TRI) possuem grande impacto na redução da pressão arterial (PA), de tal forma que podem ser usados na associação terapêutica, mas o seu benefício pode variar de acordo com o exercício praticado. A preensão palmar isométrica e agachamento na parede são exercícios que foram capazes de reduzir de forma semelhante os níveis de pressão arterial, sendo ambos praticados três vezes na semana, mas quando se reduziu a frequência para apenas uma vez na semana, somente o agachamento na parede foi capaz de manter seus benefícios e até mesmo progredir na queda da PA (Cohen, et al, 2023).…”
Section: Resultsunclassified
“…Furthermore, it is conceivable that targeted interventions and/or advice to improve muscle strength in those diagnosed with low HGS may contribute to an improved arterial health [ 18 , 41 , 75 , 76 , 77 ]. Particularly promising are the results of low-intensity isometric exercise in reducing systolic blood pressure [ 78 , 79 ], with some evidence that improvements in specific aspects of vascular function contribute to this effect [ 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…This finding may indicate accelerated adaptations with higher training frequency, which could have implications respective of the initial training phase and the potential for a subsequent reduction in training dosage during a maintenance phase. In the first IET study of its kind, Cohen et al [68] recently demonstrated that BP reductions can be maintained with a single session (handgrip or wall squat) per week following a standard 3 × weekly 12-week IET programme. These findings suggest that the traditionally employed 3 × weekly IET frequency may only be necessary during the initial training phase with potential to down-titrate frequency in a maintenance phase.…”
Section: Frequency and Detrainingmentioning
confidence: 99%